The construction of a genre. The case of service information pamphlets in a Danish county - Pedersen, Karsten (HERMES - Journal of Language and Communication in Business, 2003)
From 1999 to 2001 I was head of administrative communication in a local council in Denmark. There I was responsible for authoring and publishing service information pamphlets. I never had any complaints from the citizens who were supposed to read the pamphlets. And that made me worried. So worried that I have now spent a year analysing not only the pamphlets, but also their reception in the target population. In this article I shall make a genre analysis of the service information pamphlet and I shall compare the results of the genre analysis with the basic results of the reception analysis.